PERTANGGUNGJAWABAN NOTARIS ATAS AKTA HIBAH TANAH TAK BERSERTIFIKAT : KAJIAN HUKUM PERDATA, AGRARIA, DAN PEMBUKTIAN - Anindita Rahayu (Sebelas Maret University, 2026)
This study analyzes the legal status of deed of gift over uncertified land under Indonesian civil and agrarian law. Although such gifts are valid under civil law, uncertified land lacks legal certainty as required by agrarian regulations. Gift deeds for uncertified land serve only as preliminary evidence, not as fully authentic legal proof. PPAT’s authority is also limited for unregistered land. If disputes arise, the notary or PPAT may bear legal responsibility for negligence in verifying land status. Therefore, registering land before executing a deed of gift is crucial to prevent future legal conflicts and ensure compliance with formal requirements.